2017
DOI: 10.1021/acs.jpca.7b05002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidazole on the Electrochemistry of Zinc Porphyrins: An Electrochemical and Computational Study

Abstract: In this study, the electrochemical behavior of zinc meso-substituted porphyrins in the presence of imidazole is examined by using both cyclic voltammetry (CV) and density functional theory (DFT) methods. The results show that the first half-wave oxidation potentials (1st E) of zinc porphyrins complexed with imidazole all move to the negative side, while the second ones (2nd E) move to the positive side, resulting in larger half-wave oxidation potential splittings of the two oxidation states (ΔE = second E - fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…When compared to a model Zn(II) porphyrin, this third oxidation is effectively more difficult. In agreement with literature data [22,24], this is a diagnostic signature for a coordinated Zn(II)-porphyrin radical cation. Therefore, the complete oxidation of…”
Section: Redsupporting
confidence: 92%
See 3 more Smart Citations
“…When compared to a model Zn(II) porphyrin, this third oxidation is effectively more difficult. In agreement with literature data [22,24], this is a diagnostic signature for a coordinated Zn(II)-porphyrin radical cation. Therefore, the complete oxidation of…”
Section: Redsupporting
confidence: 92%
“…As far as the redox potential of the first oxidation is concerned, the complexation of L1 to ZnTPP leads to a smaller first ionization potential (IP 1 ) value meaning that less energy is required to oxidize the Zn(II)-porphyrin subunit in the complex. This is fully consistent with electrochemical data and DFT calculations reported for related imidazole-Zn(II)porphyrin complexes [22] and supports the assignment for E 1 ox and E 2 ox in the voltammograms obtained for compound 3. However, the second ionization potential (IP 2 ) is not in agreement with the experimental findings which revealed that the second oxidation is more difficult for complexed Zn(II)-porphyrins.…”
Section: Redsupporting
confidence: 91%
See 2 more Smart Citations
“…Porphyrins can also serve to model reactions on a simpler scale . Of these, OEPs represent a set of simple, compact, and highly studied porphyrins that form stable monolayers on a variety of metal surfaces and highly oriented pyrolytic graphite (HOPG). ,, Metallated OEPs (MOEP) have been shown to bind a variety of ligands in solution, the solid state, , and on surfaces. ,, Although the binding of imidazole and imidazole derivatives to metalloporphyrins has been previously demonstrated, few studies have reported the binding of these molecules to MOEPs, , with only one showing imidazole binding to a surface-supported OEP …”
Section: Introductionmentioning
confidence: 99%